2003
DOI: 10.1557/jmr.2003.0172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the constituents of double-walled carbon nanotubes using Raman spectra taken with different laser-excitation energies

Abstract: Double-walled carbon nanotubes (DWNTs), synthesized by the catalytic decomposition of methane, were explored by resonance Raman spectroscopy using different energies for laser excitation. Based on the radial breathing mode frequencies, the indices of the two layers of a DWNT were approximately assigned, depending on the interlayer separation of the two coaxial layers of the DWNT, which ranged from 0.34 to 0.40 nm. From the tentatively assigned results, it was found that the two walls of the DWNT are not strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Fig. 4 shows a typical Raman spectrum of our as-prepared DWNTs [14]. A Raman spectra profile similar to that of SWNTs was found for the DWNTs, which has resonantly enhanced RBM, G band and weak D band.…”
Section: Raman Spectra Of the As-prepared Dwntsmentioning
confidence: 56%
“…Fig. 4 shows a typical Raman spectrum of our as-prepared DWNTs [14]. A Raman spectra profile similar to that of SWNTs was found for the DWNTs, which has resonantly enhanced RBM, G band and weak D band.…”
Section: Raman Spectra Of the As-prepared Dwntsmentioning
confidence: 56%
“…27 The graphene and CNTs are confirmed in Figure 1e,f, and the radial breathing modes (RBMs) of the latter at 100−300 cm −1 indicate singleto few-walled CNTs (Figure 1g). 28,29 The CNTs seamlessly connect to the graphene substrate and are able to store Li ions; 27,30,31 however, due to low areal mass density, the capacity generated by the GCNTs is negligible (<0.3 mAh cm −2 ) (see Figure S2 for a detailed comparison) when compared to the GCNT-Li (up to 4 mAh cm −2 ), in which Li rather than GCNT is the active material.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 In particular, it was indicated that the stability of a DWNT depends only on the interlayer spacing, which reaches an energy minimum when the mean interlayer separation is 0.34 nm, which is independent of the chiralities of the two constituent tubes. 16 Atomistic simulations were performed to investigate the torsional behavior of abnormal DWCNTs (Fig. 2) with an interlayer distance of less than 0.34 nm (Table 1) and carbon nanowires (CNWs) made of linear carbon-atom chain (C-chain) encapsulated inside single-walled carbon nanotubes (SWCNTs) subject to torsional motion.…”
Section: Simulations/dft Calculations On Interlayer Distancesmentioning
confidence: 99%